압전 액츄에이터용 PSN-PZT 세라믹스의 압전 특성에 미치는 MnO2 첨가 효과 - 최정운; 송건화; 김한지; 윤석진; 유광수 (한국센서학회, 2007)
The effect of MnO2 as a sintering additive on the microstructures and the piezoelectric properties, especialy mechanicalquality factor, of 0.05 Pb(Sb0.5Nb0.5)O3-0.95 Pb(Zr0.52Ti0.48)O3 (PSN-PZT) piezoelectric ceramics was investigated. Thesamples were sintered at 1250oC for 2 h. The crystal structure and surface morphology of the sample were examinedusing XRD and FE-SEM, respectively. A study on the influence of MnO2 additives on the dielectric and piezoelectricproperties showed that the MnO2-added PSN-PZT system exhibited a high mechanical quality factor and well-situatedpiezoelectric properties. The optimized results of d33 (319 pC/N), kp (55 %), and Qm (751.24) were obtained at 0.2 wt%MnO2